Termite pests in eucalyptus forests of brazil - Wilcken, Carlos Frederico [UNESP]; Raetano, Carlos Gilberto [UNESP]; Forti, Luiz Carlos [UNESP] (My University, 2002)
The termite problem in eucalyptus forest plantations in Brazil has been registered since 1908. The main termite pests can be separated in four groups: a) seedling/sapling termites; b) heartwood termites; c) bark termites and d) wood termites. The termites in the first group attack root and stalk bases of young eucalyptus plants. The most common species are Syntermes spp. and Cornitermes spp. and they are a serious obstacle to early eucalyptus developing. The heartwood termites attack formed trees destroying eucalyptus heartwood. Coptotermes testaceus is the most cited species in reports, but more species probably occur. Plant mortality caused by seedling/sapling termites vary of 10-70 %. There are not effective control methods to heartwood termites. The main seedling/sapling termite control strategy is the chemical barrier around root systems of plants. Nowadays, studies are being carried out to determine monitoring systems to termite infestations. Early results indicate that proportionally, few areas really need insecticide application, due to spatial distribution of termites to be aggregated. Therefore, it is necessary to develope techniques rationalizing insecticide utilization in eucalyptus plantations, to keep production systems feasible and to be suitable for environmental exigencies.
Keywords: Forest pest; Insect damage; Pest control; Coptotermes testaceus; Cornitermes; Eucalyptus; Hexapoda; Insecta; Isoptera; Syntermes